TELAAH KRITIS TRADISI PEMIKIRAN TEOLOGI DI DUNIA PESANTREN - Khasanah, Uswatun (STAI Darul Qalam Tangerang, 2024)
Theology is a science that studies the basic teachings (fundamentals) of a religion. So this becomes very significant when someone wants to explore the ins and outs of his religion. Because theology is the basic teaching of religion, the attitude of every religious believer is actually obliged to study seriously the theology of the religion he adheres to, so that religious believers will gain a strong understanding and belief that has implications for the determination of faith. Meanwhile, if we study Islam, it is basically divided into two main components, namely aqidah and shari'ah. In approaching the problem of aqidah which concerns aspects of human belief, many are required to use aspects of thinking. In approaching the problem of shari'ah which concerns aspects of behavior, humans are required to use a lot of physical abilities (Sahal Mahfoudh, 1994: 358). It was in this issue of 'aqidah - commonly called kalam or theology - that various interpretations arose between Islamic thinkers which later gave birth to the schools of kalam or theology. In Indonesia, Islamic theology taught is generally theology in the form of tawhid. The science of monotheism is usually less in-depth in discussion and less philosophical. Furthermore, the science of tawhid usually gives one-sided discussions and does not express opinions and understandings from other schools or groups in Islamic theology. And the science of tawhid that is taught and known in Indonesia in general is the school of tawhid according to the Asy'ariah school, so that there is an impression among the Indonesian Islamic ummah, that this is the only theology that exists in Indonesia (Harun Nasution, 1986: ix-x). This fact also occurs in pesantren, where pesantren only